767 Healthy enterprise standard (hes) evaluation: analysing effects and cost-benefit results with a qualitative evaluation of implementation process. (24th April 2018) - Sultan-Taïeb, H; St-Hilaire, F; Gaillard, A; Lefebvre, R; Duchaine, C; Aubé, K; Letellier, M-C; Brisson, C; Vézina, M; Biron, C; Mantha-Bélisle, M-M
Abstract : Introduction: The Healthy Enterprise Standard (HES) is related to a certification program in Québec (Canada) and targets four areas: Lifestyle, Work-life balance, Workplace environment and Management practices . The aim of this study was to open the black box of intervention and analyse the implementation process in order to interpret effects of HES on health and workplace risk factors, and cost-benefit results from the employer's perspective. Methods: We used a before-after design for a two-case analysis with a mixed-method approach. In two organisations from different sectors, quantitative data were collected with a questionnaire among all active workers before the standard's implementation (T1 organisation A=186, organisation B=1081) and 25–31 months after (T2 A=190, B=975). Psychosocial work factors (demand-control-support and effort-reward imbalance validated scales), psychological distress (validated Kessler-6), and work-related musculoskeletal problems (WMSP, 4 items from the Nordic Questionnaire) were measured as well as intervention exposure. Intervention costs data, presenteeism and absences data were collected. Qualitative data through interviews and focus groups in both organisations were recorded, transcribed and coded in order to perform thematic analysis a posteriori. Results: The prevalence of psychosocial work factors (low social support, low reward) at T2 was lower amongst participants exposed to intervention in the Management practices area in both organisations. WMSP was lower for those exposed to the Workplace environment area in B. The average cost per worker per year was very similar for A and B whereas distribution of cost categories differed. The net benefit was highly positive in B and negative in A. Implementation analysis showed that each area of HES was associated to different types of facilitators and obstacles. Cyclical factors, communication and management involvement differed between A and B. Discussion: These results show that the implementation process analysis provides interesting insights into understanding effect and cost-benefit results and improving OSH interventions.